Syntheses, Molecular Docking Study and Anticancer Activity Examination of p-Methoxycinnamoyl Hydrazides - Melanny Ika Sulistyowati, - (International Journal of Pharmaceutical and Clinical Research, 2016)
In this study, we attempted to develop a potential anticancer drug by synthesizing some of p-methoxycinnamoyl hidrazides. The compounds were synthesized from the ethyl p-methoxycinnamate (EPMC), isolated from rhizome of Kaemferia galanga Linn. The structures of the compounds were confirmed by UV-vis spectrophotometry, 1H-NMR, 13C-NMR, FTIR, and MS spectroscopic methods. The study was followed by anticancer activity evaluation of the compounds by in silico study using Molegro® ver. 5.5 and by in vitro assay against human breast cancer cells (T47D) by 3-(4,5-Dimethylthiazol2-yl)-2-5-Diphenyltetrazolium Bromide (MTT) method. The yield of derivatives of p-methoxycinnamoylhidrazide was around 25 to 90%. The result showed that 3-(4-methoxyphenyl)-N'-(3-(4-methoxyphenyl) acryloyl) acrylohydrazide has the highest value of rerank score (-124.81). In addition, from the in vitro assay, it was revealed that 2-hydroxybenzohydrazide has the lowest IC50 (0.2 x 106 nM) against T47D as the most effective compound than the others. p-Methoxycinnamoyl hidrazides have been synthesized as low as 25% yields. Among the tested compounds, 2-hydroxybenzohydrazide is the most effective compound against T47D (human breast cancer) cell line in vitro. While in silico study result showed that 3-(4-methoxyphenyl)-N'-(3-(4-methoxyphenyl) acryloyl)acrylo- hydrazide has better activity than the lead compound, EPMC.